1987
DOI: 10.1080/00288233.1987.10430477
|View full text |Cite
|
Sign up to set email alerts
|

Hexaploid wild emmer wheat derivatives grown under New Zealand conditions 3. Influence of nitrogen fertilisation and stage of grain development on protein composition

Abstract: Hexaploid derivatives of wild emmer wheat (Triticum dicoccoides Koern.) were examined by electrophoresis for high molecular weight (HMW) glutenin subunits and for gliadin composition from 10 days after anthesis to full maturity. Two established bread wheats were included in the investigation for comparison. No outstanding or consistent differences were observed in the patterns of protein development between the wild emmer derivatives and the established bread wheats. HMW glutenin subunits were detectable in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

1987
1987
1999
1999

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
(16 reference statements)
0
4
1
Order By: Relevance
“…Previously, it has been suggested that a proportion of proteins that decrease during grain development may be broken down for reconstitution into other protein fractions at a later stage (Flint et al 1975, Cressey et al 1987. The results of our study do not seem to support this hypothesis.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Previously, it has been suggested that a proportion of proteins that decrease during grain development may be broken down for reconstitution into other protein fractions at a later stage (Flint et al 1975, Cressey et al 1987. The results of our study do not seem to support this hypothesis.…”
Section: Discussioncontrasting
confidence: 99%
“…There are two possible mechanisms affecting the accumulation and polymerization of glutenin proteins during grain development. One mechanism proposes that certain proteins break down and reconstitute to form other protein fractions at a later stage of grain development (Flint et al 1975, Cressey et al 1987. From the results of our study, we propose that a switch in mechanism in the rate of synthesis and incorporation of HMW subunits to form polymers determines the size distribution of glutenin polymers.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Developing grains were also analysed electrophoretically, to determine the time of formation and the type of the various constituent protein subunits in relation to different lines of rates of applied nitrogen (Cressey et al 1987).…”
Section: Methodsmentioning
confidence: 99%
“…Advanced breeding lines of hexaploid wild emmer wheat (Triticum dicoccoides L) derivatives developed in Israel (Grama and Gerechter Amitai 1974) have been grown and examined at Lincoln, New Zealand, to determine some of their milling and bread-making characteristics (Cressey et al 1987;Grama et al 1987a,b). SDS-PAGE was used to determine whether any unusual HMW glutenin subunits had been inherited from the wild emmer parent.…”
mentioning
confidence: 99%